RELEVANT INFORMATION ACCOUNTING AND CONTROL PROPERTIES IN ORDER TO ENSURE SUSTAINABLE ENVIRONMENTAL MANAGEMENT - I. Komissarova (Вестник университета)
In article from system line items the main organizational function blocks of information support of the tasks of increase in ecological compatibility of functioning of factors of expanded reproduction set by the user of nature are considered. Ways of solving the problem of forming of relevant information of accounting and control property for eco-friendly environmental management are offered.